IMPLEMENTASI KEBIJAKAN KESEJAHTERAAN SOSIAL LANJUT USIA DI KECAMATAN PALU BARAT KOTA PALU - Silviany, Mona (Katalogis, 2015)
Social welfare policy for elderly is a policy to improve the productivity and life quality of elderly through the program of Productive Economic Bussines. To realize the policy, the implementation is needed, so that the program of productive economic Business can increase the social welfare of elderly. The research objective is to analyze the implementation of the social welfare policy ( law No.13 of 1998 on social welfare for elderly). Social minister makes a policy of social services for elderly in the form of productive economic business program as a social investment for the productive elderly in the District of West Palu. This is a qualitative descriptive research. The data collection is through observations, interviews and documentation. The theory used is a theoretical model of policy implementation By Rippley and Franklin, due to the implementation model Rippley and Franklin emphasizes on the aspects of policy content. According to Rippley and Franklin, success of a program implementation can be viewet by the three factors; a) compliance perspective which measures obedience of apparatus; b) successful implementation is measured from the fluency routines and lack of problems, and c) a successful implementation leads to the satisfactory performance of all parties, especially the group of beneficiaries. The results showed that the implementation of the Social Welfare Policy For Elderly In The District Of West Palu has been performed well.